Increased perivascular space volume in white matter and basal ganglia is associated with cognition in Parkinson’s Disease - Erin Kaye Donahue; Ryan Patrick Foreman; Jared Joshua Duran; Michael Walter Jakowec; Joseph O’Neill; Andrew J. Petkus; Daniel P. Holschneider; Jeiran Choupan; John Darrell Van Horn; Siva Venkadesh; Ece Bayram; Irene Litvan; et al. (Brain Imaging and Behavior, 2023)
Perivascular spaces (PVS), fluid-filled compartments surrounding brain vasculature, are an essential component of the glymphatic system responsible for transport of waste and nutrients. Glymphatic system impairment may underlie cognitive deficits in Parkinson’s disease (PD). Studies have focused on the role of basal ganglia PVS with cognition in PD, but the role of white matter PVS is unknown. This study examined the relationship of white matter and basal ganglia PVS with domain-specific and global cognition in individuals with PD. Fifty individuals with PD underwent 3T T1w magnetic resonance imaging (MRI) to determine PVS volume fraction, defined as PVS volume normalized to total regional volume, within (i) centrum semiovale, (ii) prefrontal white matter (medial orbitofrontal, rostral middle frontal, superior frontal), and (iii) basal ganglia. A neuropsychological battery included assessment of global cognitive function (Montreal Cognitive Assessment, and global cognitive composite score), and cognitive-specific domains (executive function, memory, visuospatial function, attention, and language). Higher white matter rostral middle frontal PVS was associated with lower scores in both global cognitive and visuospatial function. In the basal ganglia higher PVS was associated with lower scores for memory with a trend towards lower global cognitive composite score. While previous reports have shown that greater amount of PVS in the basal ganglia is associated with decline in global cognition in PD, our findings suggest that increased white matter PVS volume may also underlie changes in cognition.

Perceptions of a Health Care Notebook from Female Breast Cancer Survivors with Cognitive Impairment - Pamela Moyo; Darrell Walters; Hilary C. Siebens; Jamie Myers; Rachel Baynes; Galen Cook-Wiens; Mi-Yeoung Jo; Arash Asher (Journal of Cancer Education, 2021)

Change in Criteria for USP Dissolution Performance Verification Tests - Walter W. Hauck; Anthony J. DeStefano; William E. Brown; Erika S. Stippler; Darrell R. Abernethy; William F. Koch; Roger L. Williams (AAPS PharmSciTech, 2009)